Candida auris Invasive Infection after Kidney Transplantation - Javier Reque; Rosa Arlandis; Nayara Panizo; Maria José Pascual; Alejandro Perez-Alba (Case Reports in Nephrology)
Introduction. C. auris has been associated not only with a variety of invasive fungal infections, including candidemia, sometimes related to central venous catheter, but also with pericarditis and respiratory tract and urinary tract infections. Materials and Methods. We describe the case of a patient with persistent fever despite antibiotics, who presented with Candida isolation in blood cultures, typified as Candida auris species. Results. A 57-year-old male receiving peritoneal dialysis underwent kidney transplantation which was complicated by primary nonfunction due to arterial thrombosis necessitating graft nephrectomy. During the postoperative period, he presented with Pseudomonas aeruginosa pneumonia that was treated with levofloxacin and catheter-related Enterococcus faecalis bacteremia treated with linezolid. After hospital discharge, he then presented with herpes zoster infection treated with valacyclovir. Ten days later, he developed peritonitis and exit site infection with multidrug-resistant Pseudomonas aeruginosa treated with intraperitoneal aztreonam and peritoneal dialysis catheter removal. Despite broad-spectrum antibiotic therapy, the patient remained febrile. All microbiology laboratory tests were negative, so it was decided to stop antibiotic therapy for 48 hours and repeat cultures in order to avoid possible false negatives. In new blood cultures performed after suspension of antibiotic therapy, candidemia was observed, later typified as Candida auris species. After completing antifungal treatment (three weeks with intravenous amphotericin B 100 mg qd and two weeks of intravenous anidulafungin 100 mg qd), microbiological cultures remained negative and the patient made uneventful recovery. Conclusion. Candida auris invasive infection has been mainly described in patients with severe underlying comorbidities and immunocompromise. Multidrug-resistant clusters of Candida auris are increasingly emerging.